Analytical and experimental study of an innovative multiple-throughout-flowing micro-channel-panels-array for a solar-powered rural house space heating system. (15th March 2019) - Fan, Yi; Zhao, Xudong; Li, Guiqiang; Cheng, Yuanda; Zhou, Jinzhi; Yu, Min; Du, Zhenyu; Ji, Jie; Zhu, Zishang; Diallo, Thierno; Ma, Xiaoli
Abstract: This paper presents a combined analytical and experimental study of an innovative multiple-throughout-flowing micro-channel-panels-array applicable to a solar-powered rural house space heating system. This array, compared to the traditional one-to-one-connection panels-array, can significantly reduce the temperature difference between the head and real panels and thus increase the overall solar thermal efficiency and energy efficiency ratio (EER). The research methodology covers the theoretical analysis, experimental testing, model validation and system optimization. It is found that the analytical model has a good accuracy in predicting the performance of the multiple-throughout-flow micro-channels-panels-array, giving a discrepancy of less than 10%. In terms of the configuration and sizes of the array, 10 pieces of panels with 5 flow turns is regarded as the most favorite option. During the operation, decreasing flow rate of the fluid led to the increased EER of the panels-array. By converting the one-to-one-connection mode into the multiple-throughout-flowing mode, the overall solar thermal efficiency of the panels-array increases by around 10% and its energy efficiency factor (EER) decreases by 80% respectively. The research has addressed a novel solar-panels-array that can be well applied to solar thermal systems, thus making a significant contribution to the saving of fossil fuel energy consumption and reduction of carbon emission on global scale. Highlights: Multiple-throughout-flow lowers temperature difference between head and rear panels. This flow mode leads to the increased overall solar thermal efficiency by around 10%. This flow mode leads to the increased energy efficiency factor by around 80%. The most appropriate panel number in an array is 10. The most appropriate fluid flow turning number is 5.